(untitled) (Public Sector Economics - submission site, 2023)
In this paper, we carry out an in-depth analysis of public expenditure in all former Yugoslavian countries. Our purpose is threefold: first, to verify the existence of common patterns of spending; second, to investigate the cyclicality hypothesis of fiscal policy in non-OECD countries; and third, to analyse both political and economic determinants of expenditure composition. Our results show a weak convergence in structures, the countercyclical behaviour of public expenditures, and the influence of electoral cycles, business cycles, and the degree of nationalization of party systems on the composition of public expenditure.